OPTIMALISASI PEMUNGUTAN RETRIBUSI PARKIR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (STUDI PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA KENDARI) - Insani, Nurul; Mustakim, Mustakim; Sartono, Sartono (Universitas Halu Oleo, 2020)
The purpose of this study is to find out how to Optimize Parking Levy Collection in Increasing Local Revenue and To Know What Factors Affect Parking Levy Collection. Data collection techniques using observation, interviews and documentation. The number of informants in this study was 5 people. The results of the study explained that the Optimization of Parking Levy Collection in Increasing Local Revenue is quite good, In the collection of parking fees the Kendari City Regional Tax and Retribution Management Agency (BP2RD) of Kendari City has tried to carry out its duties, especially in achieving parking targets, even though it still encounters several obstacles in implementation of parking levies collection.